Pengaruh Literasi Keuangan dan Gaya Hidup terhadap Pengelolaan Keuangan Mahasiswa Program Studi Manajemen Universitas Pamulang - Naela Farkhati; Agus Supriatna (Moneter : Jurnal Ekonomi dan Keuangan, 2026)
This study aims to analyze the effect of financial literacy and lifestyle on financial management of students of the Management Study Program at Universitas Pamulang. This research uses a quantitative method with an associative approach, with data collected through questionnaires distributed to 160 respondents. Data analysis was conducted using validity tests, reliability tests, classical assumption tests, simple and multiple linear regression analysis, t-test, F-test, and coefficient of determination (R²). The results show that partially financial literacy has a positive and significant effect on financial management with a t-value of 7,161 > t-table 1.975 and a significance value of 0.000 < 0.05, while lifestyle also has a positive and significant effect with a t-value of 6,881 > t-table 1.975 and a significance value of 0.000 < 0.05. Simultaneously, financial literacy and lifestyle have a significant effect on financial management with an F-value of 853.671 > F-table 3.05 and a significance value of 0.000 < 0.05. The coefficient of determination of 0.916 indicates that 91,6% of the variation in students’ financial management is explained by financial literacy and lifestyle, while the remaining 8,4% is influenced by other factors outside this study.